On Right (σ,τ)- Derivation of Prime Rings - Majeed, A.; Hamdi, Asawer (Iraqi Journal of Science, 2024)
Let R be a prime ring and δ a right (σ,τ)-derivation on R. In the present paper we will prove the following results:First, suppose that R is a prime ring and I a non-zero ideal of R if δ acts as a homomorphism on I then δ=0 on R, and if δ acts an anti- homomorphism on I then either δ=0 on R or R is commutative.Second, suppose that R is 2-torsion-free prime ring and J a non-zero Jordan ideal and a subring of R, if δ acts as a homomorphism on J then δ=0 on J, and if δ acts an anti- homomorphism on J then either δ=0 on J or JZ(R).